Strategi Penerjemahan Takarir Film Buya Hamka Vol.1 dan Implikasinya terhadap Pengajaran Penerjemahan - Lafziatul Hilmi; Syihabbuddin Syihabbuddin (Neolectura, 2024)
The existences of subtitling (a part of audiovisual translation) in assisting people from other countries to enjoy movies have been new breakthroughs yet challenges to film industries. Nowadays, many Indonesian movies present the richness of local languages such as Javanese language, Minangkabau language, Batak language, and other local languages accompanied by English subtitles, so the movies can be watched not only by Indonesian audiences, but also viewers from other countries. One of the movies is Buya Hamka Vol.1 movie. This study aims to reveal the subtitling strategies used in Buya Hamka Vol.1 movie and its implication to teaching translation. This was a qualitative study with content analysis design. The data were the excerpts of conversations using Minangkabaunese (source language) compared to the correspond English (target language) subtitle provided by Netflix, and were analysed by using subtitling strategies theory by Gottlieb. The result showed that transfer is the most frequently strategy found in the study because of the common word order pattern employed in Minangkabaunese and English.